Analisis Kos Produksi UMKM Kuliner Menggunakan Metode Job Order Costing dan Process Costing di Kota Jambi - Rifka Adelia; Nasya Mykayla; Annisa Irawanti; Mellya Embun Baining (International Forum of Researchers and Lecturers, 2026)
This research examines the use of Job Order Costing at BuyBubMelts (fried dimsum) and Process Costing at Kopitiam 72 (mie tek tek) in Jambi City. The aim is to evaluate the calculation outcomes of cost of goods manufactured (COGM) and profit margins across the two approaches. Data were gathered by means of observation, interviews, and the documentation of production expenses. Findings indicate that BuyBubMelts, utilizing Job Order Costing, generated a unit cost of IDR 18,000 with a profit margin of 10%, whereas Kopitiam 72, employing Process Costing, yielded a unit cost of IDR 7,450 with a profit margin of 28%. These findings emphasize that cost accounting techniques should match the traits of the business: production based on orders usually incurs higher unit costs and has tighter margins, while mass production is generally more efficient and produces steadier profits. Suggestions involve enhancing raw material efficiency, innovating menus, and implementing premium pricing strategies for order-oriented UMKM, whereas process-oriented UMKM ought to concentrate on boosting production capacity and utilizing digital marketing.